IMPLEMENTATION OF VILLAGE FINANCIAL MANAGEMENT SUPERVISION POLICY BY GOVERNMENT INTERNAL SUPERVISOR APPARATUS - Rezeky, Aiman Sabar; Nawawi, Juanda; Syamsu, Suhardiman (Universitas Djuanda, 2024)
Village financial governance, which is often identified with corruption and abuse in terms of its management, must be accompanied by a supervisory system by the government and the community to minimize potential irregularities. This research aims to provide an analytical description of the implementation of Permendagri Number 73 of 2020 concerning the Supervision of Village Financial Management by Government Internal Supervisor Apparatus. The method used is qualitative research. The data collection techniques include interviews, observation, documentation, and literature study. The Associate Expert Auditor of the Gowa Regency Inspectorate became the main informant in this research. Data analysis is carried out through data reduction, presentation, and verification. By referring to Edward III's Policy Implementation theory, the results show that the communication, disposition, and bureaucratic structure variables have been running quite well. However, the resource variable still needs to be constrained by the quantity of human resources who carry out the policy and the lack of supervision budget. The factors inhibiting the supervision of village financial management for APIP Gowa Regency are generally influenced by two factors, namely delays in completing supervisory recommendations and changes in village treasurers.